Chemokine signaling links cell-cycle progression and cilia formation for left–right symmetry breaking - Liu, Jingwen; Zhu, Chengke; Ning, Guozhu; Yang, Liping; Cao, Yu; Huang, Sizhou; Wang, Qiang (PLOS Biology, 2019)
Zebrafish dorsal forerunner cells (DFCs) undergo vigorous proliferation during epiboly and then exit the cell cycle to generate Kupffer’s vesicle (KV), a ciliated organ necessary for establishing left–right (L–R) asymmetry. DFC proliferation defects are often accompanied by impaired cilia elongation in KV, but the functional and molecular interaction between cell-cycle progression and cilia formation remains unknown. Here, we show that chemokine receptor Cxcr4a is required for L–R laterality by controlling DFC proliferation and KV ciliogenesis. Functional analysis revealed that Cxcr4a accelerates G1/S transition in DFCs and stabilizes forkhead box j1a (Foxj1a), a master regulator of motile cilia, by stimulating Cyclin D1 expression through extracellular regulated MAP kinase (ERK) 1/2 signaling. Mechanistically, Cyclin D1–cyclin-dependent kinase (CDK) 4/6 drives G1/S transition during DFC proliferation and phosphorylates Foxj1a, thereby disrupting its association with proteasome 26S subunit, non-ATPase 4b (Psmd4b), a 19S regulatory subunit. This prevents the ubiquitin (Ub)-independent proteasomal degradation of Foxj1a. Our study uncovers a role for Cxcr4 signaling in L–R patterning and provides fundamental insights into the molecular linkage between cell-cycle progression and ciliogenesis.